2012
DOI: 10.1021/jf302757j
|View full text |Cite
|
Sign up to set email alerts
|

Elongation and Desaturation Pathways in Mammary Gland Epithelial Cells Are Associated with Modulation of Fat and Membrane Composition

Abstract: The aim was to determine the relative role of each of the lactogenic hormones (insulin, prolactin and hydrocortisol) and their combinations in regulating elongation and desaturation of polyunsaturated fatty acids and subsequently on composition of cellular lipid compartments in mammary epithelia. Cultured cells of the mammary gland epithelial cell line HC11 were subjected to 48 h of hormonal treatment with different combinations of insulin, hydrocortisone and prolactin. Only the combination of all three hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Probability of relapse-free survival in all breast cancers, HR, and log-rank test were calculated for analysis of significance. insulin, cortisol, and prolactin induced Fads2 and Elovl6 expression that was consistent with C16:0 reduction and C16:1 increase compared with results for incubation with each hormone separately (47). Our results are in agreement with these studies and provide further evidence of consistency in reproducing functional differentiation of HC11 cells in vitro.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Probability of relapse-free survival in all breast cancers, HR, and log-rank test were calculated for analysis of significance. insulin, cortisol, and prolactin induced Fads2 and Elovl6 expression that was consistent with C16:0 reduction and C16:1 increase compared with results for incubation with each hormone separately (47). Our results are in agreement with these studies and provide further evidence of consistency in reproducing functional differentiation of HC11 cells in vitro.…”
Section: Discussionsupporting
confidence: 90%
“…The HC11 cell line has long been used to study lactogenic hormone effects on gene and protein expression in MECs. Regarding lipid metabolism, it was only recently shown that a combination of the lactogenic hormones insulin, cortisol, and prolactin induced Fads2 and Elovl6 expression that was consistent with C16:0 reduction and C16:1 increase compared with results for incubation with each hormone separately (47). Our results are in agreement with these studies and provide further evidence of consistency in reproducing functional differentiation of HC11 cells in vitro .…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported in studies in humans, that the intake of fats such as SO modifies the effects of the polymorphism of the ELOVL6 gene, suggesting a relationship between these two factors [37]. Recently, the expression of ELOVL6 in murine mammary epithelial cells has been demonstrated in vitro [38]. However, determining its roles in ruminant mammary lipid metabolism and in the milk FA composition will require further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are components of cell membranes, and FA provided in the media of cultured mammary epithelial cells are primarily incorporated into cell membrane phospholipids ( Mida et al., 2012 ). The relative amounts of SFA and UFA, as well as chain length of FA that constitute membranes, are important factors that determine membrane fluidity.…”
Section: Resultsmentioning
confidence: 99%